A Study on Ethical Implications, Trust, and Audit Reliability in AI Assisted Accounting: An Extended UTAUT Perspective in Emerging Economies (The Journal of Theoretical Accounting Research, 2025)
Purpose: This paper examines how ethical perception and trust shape the adoption and reliability of artificial intelligence systems in accounting and auditing, particularly within emerging economies. It extends the Unified Theory of Acceptance and Use of Technology (UTAUT) to incorporate ethical and trust-based dimensions that influence professional acceptance beyond functional factors.Design/methodology/approach: A conceptual framework is proposed by integrating ethical perception and trust into the traditional UTAUT model. The framework highlights their moderating and mediating roles in linking performance expectancy, behavioural intention, and audit reliability. Insights from existing literature and theoretical reasoning support the development of this extended model.Findings: The study argues that AI adoption in professional accounting contexts is both a technological and moral process. Ethical perception strengthens trust, and together they enhance responsible adoption, critical engagement, and audit reliability. The framework positions moral legitimacy and institutional trust as essential conditions for sustainable AI integration.Practical implications: For practitioners and audit firms, embedding ethical design principles, algorithmic transparency, and human oversight in AI systems can foster greater trust and accountability. For regulators, establishing AI audit assurance frameworks and updating ethical codes can help manage risks associated with automation in professional judgment.Social implications: The framework emphasises the need for ethical governance and professional readiness in emerging economies, where rapid technological adoption can outpace institutional safeguards. Promoting ethical AI awareness can strengthen confidence in technology and enhance the integrity of financial reporting.Originality/value: This paper contributes to technology adoption literature by reconceptualising AI use in accounting as an ethically anchored process. It shifts the discussion from efficiency and usability to accountability, transparency, and professional trust, offering a foundation for future empirical studies in emerging markets.